Family - a procreative institution and the Christian sociopsychological and religious perception of abortion traumas - Nina Stănescu (Technium Social Sciences Journal, 2020)
In the political and social life of the last centuries, almost every social aspect has been debated in a context of political influences and interests, of the opposition of different groups of more or less political nature. The family has always been the most favorable environment for the birth and perfection of the human being. The procreation, care, upbringing and preparation for life of a new creature have been and are a fundamental concern of any family. Children represent the "golden fund of a people" and maintain the natural human potential, give natural and spiritual strength to a people. One of the aspects that received special attention was the right of women to have a say in their own reproduction, namely the right of women to choose whether or not to keep a pregnancy. Immoral in terms of the Church, outlawed by the legislation of some states, the right to abortion has had a sinuous evolution on the social scene of many states. This issue has many political, moral and social connotations, being politically regulated differently by different states.